INFLUENCE COMPENSATION, CAREER DEVELOPMENT AND JOB SATISFACTION TO TURNOVER INTENTION - Yonathan Purba, Margo; Sangkala Ruslan (Dinasti International Journal of Economics, Finance & Accounting, 2020)
The purpose of this study aims to test and analyze the effect of compensation, career development and job satisfaction on employee turnover intentions at PT. XYZ Research data is data collected from interviews, questionnaires and supporting data from PT. XYZ for 3 consecutive years from 2016 to 2018. The sampling method used is the saturation sampling method. From a population of 156 people, the sample used was 113 people as well. The analytical method used in this study is multiple linear regression analysis. The results showed compensation, career development and job satisfaction together (simultaneously) significantly influence turnover intention. Partially shows that compensation has a negative and significant effect on turnover intention. Career development has a negative and significant effect on turnover intentions. Job satisfaction has a negative and significant effect on turnover intentions